2016
DOI: 10.1016/j.jclinepi.2016.01.030
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of Simpson's paradox if site-level effect was ignored in the TREAT Asia HIV Observational Database

Abstract: Background In multi-site HIV observational cohorts, clustering of observations often occur within sites. Ignoring clustering may lead to “Simpson's paradox” (SP) where the trend observed in the aggregated data is reversed when the groups are separated. This study aimed to investigate the SP in an Asian HIV cohort and the effects of site-level adjustment through various Cox-regression models. Methods Survival time from combination antiretroviral therapy (cART) initiation was analysed using four Cox models: (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We believe this is appropriate as sites without TB cases, even in the same country, could have quite different patient populations, thus potentially biasing risk factor models. 14,20 The power of analyses, which depends on the number of TB cases, is largely unaffected by this approach. A sensitivity analysis including participants at sites with no TB cases from the same countries as the study sites was performed (data not shown), and a lower TB incidence rate of 2.5 per 100 person-years was observed.…”
Section: Discussionmentioning
confidence: 99%
“…We believe this is appropriate as sites without TB cases, even in the same country, could have quite different patient populations, thus potentially biasing risk factor models. 14,20 The power of analyses, which depends on the number of TB cases, is largely unaffected by this approach. A sensitivity analysis including participants at sites with no TB cases from the same countries as the study sites was performed (data not shown), and a lower TB incidence rate of 2.5 per 100 person-years was observed.…”
Section: Discussionmentioning
confidence: 99%
“…All analyses were stratified by site to account for the potential disparities in health care systems and differences in clinical practices across the participating sites 16 . A two‐sided level of 5% statistical significance was used for all inferences.…”
Section: Methodsmentioning
confidence: 99%
“…All analyses were stratified by site to account for the potential disparities in health care systems and differences in clinical practices across the participating sites. 16 A twosided level of 5% statistical significance was used for all inferences. The analyses were performed using sas software version 9.4 (SAS Institute, Cary, NC) and stata software version 14.2 (STATA Corp.).…”
Section: Metabolic Syndrome and Allcause Mortalitymentioning
confidence: 99%